Self-assembled monolayer material, preparation method and application thereof, and perovskite solar cell
Patent Information
- Application Number
- CN202610964404.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0005]本发明的目的是为了克服现有技术中自组装单分子层(SAMs)与钙钛矿界面之间的作用力较弱,使得钙钛矿太阳能电池的光电转化效率较低的问题,提供了一种自组装单分子层材料及其制备方法与应用、钙钛矿太阳能电池
本发明提供的自组装单分子层材料一端含有二硫代氨基甲酸(甲酸盐)基团,能够与钙钛矿中的B位金属离子形成强螯合作用,提供成核位点并钝化界面缺陷;另一端咔唑类基团,能够通过π-π相互作用增强钙钛矿与传输层之间的界面耦合,从而提高空穴提取效率,最终提升钙钛矿太阳能电池的光电转换效率、开路电压(Voc)和填充因子(FF)。
Smart Images

Figure CN122916902A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of new energy materials technology, specifically to a self-assembled monolayer material, its preparation method and application, and perovskite solar cells. Background Technology
[0002] Self-assembled monolayers (SAMs) have shown great potential as hole transport layers in solar cells, but their weak interactions with perovskite interfaces introduce a series of drawbacks that cannot be ignored. Weakly interacting interfaces typically contain a large number of defect states, such as uncoordinated lead ions (Pb²⁺). + ) and iodine vacancy (V i These defects become strong recombination centers, severely reducing the open-circuit voltage (Voc) of solar cells and impairing photoelectric conversion efficiency.
[0003] Furthermore, the transfer of holes from perovskite to SAMs and then to the electrodes requires efficient interfacial coupling. Weak interactions slow down this extraction kinetics, leading to the accumulation of photogenerated charges at the interface, which in turn increases recombination losses and reduces short-circuit current density and fill factor.
[0004] Therefore, there is an urgent need to develop a novel self-assembled monolayer material with high hole extraction efficiency, which will ultimately improve the photoelectric conversion efficiency, open-circuit voltage (Voc), and fill factor of solar cells. Summary of the Invention
[0005] The purpose of this invention is to overcome the problem that the interaction between self-assembled monolayers (SAMs) and the perovskite interface is weak in the prior art, resulting in low photoelectric conversion efficiency of perovskite solar cells. This invention provides a self-assembled monolayer material, its preparation method and application, and perovskite solar cells.
[0006] To achieve the above objectives, the first aspect of the present invention provides a self-assembled monolayer material having a structure shown in Formula I-1 or Formula I-2; Formula I-1; Formula I-2; Among them, R a1 and R b1 Each is an independently substituted or unsubstituted carbazole group; R a2 and R b2 Each is independently a C1-C8 alkylene group or a C6-C12 arylene group; M + It is a monovalent cation.
[0007] A second aspect of the present invention provides a method for preparing a self-assembled monolayer material, the method comprising: S1-1, In the presence of a first inorganic base and a phase transfer catalyst, compound E1 and compound E2 are contacted in a first solvent to carry out a first reaction, yielding a first intermediate; S1-2. In the presence of a palladium catalyst, compound F1 and compound F2 are brought into contact for a cross-coupling reaction, followed by a reduction reaction in the presence of a reducing agent and a reduction catalyst to obtain the first intermediate. S2. In the second solvent, the first intermediate obtained in step S1-1 or step S1-2 is contacted with an acid to carry out a second reaction to obtain the second intermediate. S3. In the third solvent, the second intermediate is contacted with the second inorganic base to carry out the third reaction. The liquid after the reaction is reacted with carbon disulfide in the presence of the third inorganic base to carry out the fourth reaction. After the reaction, the pH of the system is adjusted to acidic. After solid-liquid separation, the self-assembled monolayer material 1 is obtained. S4. Optionally, the above self-assembled monolayer 1 is contacted with an alkaline compound in a fourth solvent to carry out a fifth reaction, and after solid-liquid separation, the self-assembled monolayer material 2 is obtained. Among them, compound E1 has the structure shown in formula (1); Equation (1); Compound E2 has the structure shown in formula (2); Equation (2); Compound F1 has the structure shown in formula (3); Equation (3); Compound F2 has the structure shown in formula (4); Equation (4); Where X is a halogen; R2' is a C1-C8 alkylene group or a C6-C12 arylene group; R is a C2-C18 alkyl group; R' 1-1 、R' 1-2 、R'' 1-1 、R'' 1-2 Each can be independently H, phenyl, methyl, or methoxy; R1 is a C1-C8 alkyl group; R3 is a C1-C8 alkyl group, and p is an integer from 1 to 10.
[0008] A third aspect of the present invention provides a self-assembled monolayer material prepared by the preparation method described above.
[0009] The fourth aspect of this invention provides the application of the self-assembled monolayer material as described above in perovskite solar cells.
[0010] The fifth aspect of the present invention provides a perovskite solar cell, the perovskite solar cell comprising: a substrate, a hole transport layer, a perovskite active layer, an electron transport layer, and an electrode; The hole transport layer comprises a metal oxide and a self-assembled monolayer material as described above.
[0011] Through the above technical solution, the present invention can achieve at least the following beneficial effects: The self-assembled monolayer material provided by this invention contains a dithiocarbamate (formate) group at one end, which can form a strong chelation with B-site metal ions in perovskite, providing nucleation sites and passivating interface defects; the other end contains a carbazole group, which can enhance the interfacial coupling between perovskite and transport layer through π-π interaction, thereby improving hole extraction efficiency and ultimately improving the photoelectric conversion efficiency, open-circuit voltage (Voc), and fill factor (FF) of perovskite solar cells. Attached Figure Description
[0012] Figure 1 This is the 1H NMR spectrum of the self-assembled monomolecular material A1 prepared in Example 1. Detailed Implementation
[0013] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0014] The first aspect of the present invention provides a self-assembled monolayer material having a structure shown in Formula I-1 or Formula I-2; Formula I-1; Formula I-2; Among them, R a1 and R b1 Each is an independently substituted or unsubstituted carbazole group; R a2 and R b2 Each is independently a C1-C8 alkylene group or a C6-C12 arylene group; M + It is a monovalent cation.
[0015] In this invention, the self-assembled monolayer material contains a dithiocarbamate (formate) group at one end, which can form a strong chelation with metal ions (especially lead ions) in perovskite, providing nucleation sites and passivating interface defects; the carbazole group structure at the other end can enhance the interfacial coupling between perovskite and transport layer through π-π interaction, thereby improving hole extraction efficiency. In particular, using it as part of the hole transport layer of lead-based perovskite solar cells can effectively improve the photoelectric conversion efficiency, open-circuit voltage (Voc), and fill factor (FF) of solar cells.
[0016] In this invention, the term "carbazole group" has the conventional meaning in the art, referring to a class of compounds containing... Structure and / or The structural group. "Substituted carbazole group" refers to a group in which at least one H atom of C is replaced by another element or substituent.
[0017] In this invention, This indicates the position where the carbazole group is attached to the compound shown in Formula I-1 or Formula I-2.
[0018] According to the present invention, preferably, R a1 and R b1 Each is an independent group represented by Formula II; Formula II; Among them, R 1-1 and R 1-2 Each can be independently H, phenyl, methyl, or methoxy.
[0019] In this invention, R a1 Or R b1 When the groups are of the above types, it is more conducive to the orderly and dense arrangement of self-assembled molecules and reduces the defect density on the perovskite surface.
[0020] According to the present invention, preferably, R a2 and R b2 Each is independently a C2-C4 alkylene or phenylene.
[0021] In this invention, R a2 Or R b2 When the radicals are of the types mentioned above, it is more conducive to carrier transport and improves the photoelectric conversion efficiency of solar cells.
[0022] According to the present invention, preferably, M + For Li + Na + K + 、Rb + Cs + NH4 +R3NH3 + Or (R4)4N + In this context, R3 and R4 are each independently a C1-C3 alkyl group.
[0023] In some specific embodiments of the present invention, the self-assembled monolayer material has the structure shown in Formula III-1, Formula III-2, Formula III-3 or Formula III-4; Formula III-1; Formula III-2; Formula III-3; Formula III-4.
[0024] A second aspect of the present invention provides a method for preparing a self-assembled monolayer material, the method comprising: S1-1, In the presence of a first inorganic base and a phase transfer catalyst, compound E1 and compound E2 are contacted in a first solvent to carry out a first reaction, yielding a first intermediate; S1-2. In the presence of a palladium catalyst, compound F1 and compound F2 are brought into contact for a cross-coupling reaction, followed by a reduction reaction in the presence of a reducing agent and a reduction catalyst to obtain the first intermediate. S2. In the second solvent, the first intermediate obtained in step S1-1 or step S1-2 is contacted with an acid to carry out a second reaction to obtain the second intermediate. S3. In the third solvent, the second intermediate is contacted with the second inorganic base to carry out the third reaction. The liquid after the reaction is reacted with carbon disulfide in the presence of the third inorganic base to carry out the fourth reaction. After the reaction, the pH of the system is adjusted to acidic. After solid-liquid separation, the self-assembled monolayer material 1 is obtained. S4. Optionally, the above self-assembled monolayer 1 is contacted with an alkaline compound in a fourth solvent to carry out a fifth reaction, and after solid-liquid separation, the self-assembled monolayer material 2 is obtained. Among them, compound E1 has the structure shown in formula (1); Equation (1); Compound E2 has the structure shown in formula (2); Equation (2); Compound F1 has the structure shown in formula (3); Equation (3); Compound F2 has the structure shown in formula (4); Equation (4); Where X is a halogen; R2' is a C1-C8 alkylene group or a C6-C12 arylene group; R is a C2-C18 alkyl group; R' 1-1 、R' 1-2 、R'' 1-1 、R'' 1-2 Each can be independently H, phenyl, methyl, or methoxy; R1 is a C1-C8 alkyl group; R3 is a C1-C8 alkyl group, and p is an integer from 1 to 10.
[0025] In this invention, the self-assembled monolayer material 1 shown in Formula I-1 can be obtained through step S3, and further, the self-assembled monolayer material 2 shown in Formula I-2 can be obtained through step S4.
[0026] In one specific embodiment of the present invention, the first intermediate is prepared according to step S1-1.
[0027] According to the present invention, preferably, the first inorganic base is KOH and / or NaOH.
[0028] In this invention, the amount of the first inorganic base is not particularly limited and can be selected according to actual needs, as long as it can provide the OH required for the reaction. - That's all.
[0029] According to the present invention, preferably, the phase transfer catalyst is selected from at least one of tetrabutylammonium bromide, tetrabutylammonium chloride and benzyltriethylammonium chloride.
[0030] According to the present invention, preferably, the molar ratio of the phase transfer catalyst to compound E1 is 0.1-0.2:1.
[0031] In this invention, the type and amount of the first solvent are not particularly limited, as long as they can uniformly dissolve and disperse the material and provide a stable reaction environment. For example, it can be a mixed solution of acetone and water, with a volume ratio of acetone to water of 1:5-10.
[0032] According to the present invention, preferably, the molar ratio of compound E1 to compound E2 is 1:1-2.
[0033] According to the present invention, preferably, the conditions for the first reaction include: being carried out under a protective atmosphere, at a temperature of 50-60°C, and for a time of 8-16 h.
[0034] In this invention, the protective atmosphere can be provided by a protective gas conventionally selected in the art. For example, it can be provided by nitrogen.
[0035] In this invention, the preparation method further includes post-processing after the first reaction to obtain the first intermediate.
[0036] More preferably, the post-processing includes, but is not limited to, extraction, concentration, and purification. The methods for extraction, concentration, and purification can be conventional choices within the art.
[0037] In some specific embodiments of the present invention, after the first reaction, the product is extracted with a mixed solution of dichloromethane and water (the volume ratio of dichloromethane to water is 0.5-2:1), the extracted organic layer is concentrated by rotary evaporation, and the crude product is purified by column chromatography to obtain the first intermediate.
[0038] In another specific embodiment of the present invention, the first intermediate is prepared according to steps S1-2.
[0039] According to the present invention, in steps S1-2, the molar ratio of compound F1 to compound F2 is 1:1-1.5.
[0040] In a preferred embodiment of the present invention, in formula (4), p is an integer from 1 to 4.
[0041] In a preferred embodiment of the present invention, in formula (4), R3 is a C1-C6 branched alkyl group, more preferably a tert-butyl group.
[0042] In one specific embodiment of the present invention, compound F2 is N-Boc-allylamine (i.e., in formula (4), p=1 and R3 is tert-butyl).
[0043] In this invention, in steps S1-2, the cross-coupling reaction is carried out in the presence of a solvent and an acid adsorbent. In this invention, the solvent for the cross-coupling reaction is not particularly limited, as long as it allows the cross-coupling reaction to proceed smoothly; for example, dioxane. In this invention, the type of acid adsorbent is also not particularly limited; any compound that can combine with the hydrogen halide byproduct generated in the cross-coupling reaction and promote the smooth progress of the cross-coupling reaction is acceptable; for example, the acid adsorbent is N-methyldicyclohexylamine.
[0044] According to the present invention, in steps S1-2, the molar ratio of the palladium catalyst to the compound F1 is 0.01-0.05:1.
[0045] In this invention, there is no particular limitation on the type of palladium catalyst, as long as it enables the cross-coupling reaction between compound F1 and the protected amine compound containing a double bond. For example, the palladium catalyst is selected from bis(tri-tert-butylphosphine)palladium.
[0046] In this invention, steps S1-2 also include a step of purifying the product of the cross-coupling reaction. There are no particular limitations on the purification method, as long as a pure coupling product containing double bonds can be obtained.
[0047] According to the present invention, there are no particular limitations on the reducing agent and reducing catalyst used in the reduction reaction, as long as the double bond in the coupling product containing the double bond is eliminated to obtain the first intermediate. For example, in step S1-2, the reducing agent is selected from triethylsilane; in step S1-2, the reducing catalyst is selected from Pd / C.
[0048] In this invention, preferably, the reduction reaction takes place in the presence of a solvent. The solvent for the reduction reaction is not particularly limited, as long as it allows the coupling product containing the double bond to be fully dissolved and dispersed in the solvent, ensuring the smooth progress of the reduction reaction. For example, the solvent for the reduction reaction can be a mixture of dioxane and ethanol. The volume ratio of dioxane to ethanol in the mixed solvent is not particularly limited and can be adjusted according to actual needs.
[0049] According to the present invention, in steps S1-2, the conditions for the cross-coupling reaction include: being carried out under a protective atmosphere, at a temperature of 75-85°C, and for a time of 16-24 hours.
[0050] According to the present invention, in steps S1-2, the conditions for the reduction reaction include: a temperature of 30-40°C and a time of 2-4 hours.
[0051] In this invention, the type and amount of the second solvent are not particularly limited, as long as they can ensure uniform dissolution and dispersion of the material and provide a stable reaction environment. For example, it can be 1,4-dioxane.
[0052] According to the present invention, preferably, the acid is selected from at least one of hydrochloric acid, sulfuric acid and phosphoric acid.
[0053] In this invention, the amount of acid used is not particularly limited and can be selected according to actual needs, as long as it can provide the H+ required for the reaction. + That's all.
[0054] According to the present invention, preferably, the conditions for the second reaction include: being carried out in a light-proof and protective atmosphere at a temperature of 40-50°C for 5-6 hours.
[0055] More preferably, the conditions for the second reaction include: being carried out in a light-proof and protective atmosphere at a temperature of 42-47°C.
[0056] In this invention, the preparation method further includes post-processing after the second reaction to obtain the second intermediate.
[0057] More preferably, the post-processing includes, but is not limited to, concentration and phase separation. The methods for concentration and phase separation can be conventional choices within the art.
[0058] In some specific embodiments of the present invention, after the second reaction, the solvent is removed by rotary evaporation, ethanol is added to dissolve the solid, and then diethyl ether is added to precipitate the solid, thus obtaining the second intermediate.
[0059] In this invention, the type and amount of the third solvent are not particularly limited, as long as it can uniformly dissolve and disperse the material and provide a stable reaction environment. For example, it can be ethanol.
[0060] According to the present invention, preferably, the second inorganic base is KOH and / or NaOH.
[0061] In this invention, the amount of the second inorganic base is not particularly limited and can be selected according to actual needs, as long as it can provide the OH required for the reaction. - That's all.
[0062] In this invention, the third reaction can be carried out at room temperature (23±3℃).
[0063] According to the present invention, preferably, the third reaction takes 1-2 hours.
[0064] More preferably, the third reaction takes 1-1.2 h.
[0065] In this invention, the preparation method further includes solid-liquid separation after the third reaction to remove the generated solid. The solid-liquid separation method can be a conventional choice within the art.
[0066] According to the present invention, preferably, the third inorganic base is KOH and / or NaOH.
[0067] In this invention, the amount of the third inorganic base is not particularly limited and can be selected according to actual needs, as long as it can provide the OH required for the reaction. - That's all.
[0068] In this invention, to improve temperature stability during the reaction process, the third inorganic base is added under ice bath conditions (0℃±4℃).
[0069] According to the present invention, preferably, the molar ratio of carbon disulfide to compound E1 is 1-1.2:1.
[0070] In this invention, the fourth reaction can be carried out at room temperature (23±3℃).
[0071] According to the present invention, preferably, the fourth reaction takes 1-2 hours.
[0072] More preferably, the fourth reaction takes 1-1.5 hours.
[0073] In this invention, the pH of the system can be adjusted to acidic by adding an optional inorganic acid after the fourth reaction.
[0074] More preferably, the pH of the system is adjusted to 4-6.
[0075] In this invention, the solid-liquid separation described in step S3 can be performed simultaneously with purification. For example, solid-liquid separation and purification can be achieved by repeatedly evaporating ethanol into the system.
[0076] In this invention, the amount of alkali compound containing the alkali metal element is such that the OH group therein... - With H in the self-assembled monolayer 1 of Formula I-1 containing dithiocarbamic acid structure + After a complete reaction, a self-assembled monolayer material 2, represented by Formula I-2, containing a dithiocarbamate structure, is obtained.
[0077] In this invention, the alkali compound can be an organic alkali or an inorganic alkali.
[0078] In this invention, the type and amount of the fourth solvent are not particularly limited, as long as they can ensure uniform dissolution and dispersion of the material and provide a stable reaction environment. For example, it can be ethanol.
[0079] In this invention, the time for the fifth reaction is 0.5-2 h.
[0080] In this invention, the solid-liquid separation method described in step S4 can be a conventional choice within the art. For example, solid-liquid separation can be achieved by removing the fourth solvent through rotary evaporation.
[0081] A third aspect of the present invention provides a self-assembled monolayer material prepared by the preparation method described above.
[0082] The fourth aspect of this invention provides the application of the self-assembled monolayer material as described above in perovskite solar cells.
[0083] The fifth aspect of the present invention provides a perovskite solar cell, the perovskite solar cell comprising: a substrate, a hole transport layer, a perovskite active layer, an electron transport layer, and an electrode; The hole transport layer comprises a metal oxide and a self-assembled monolayer material as described above.
[0084] In this invention, the substrate can be a solar cell substrate conventionally selected in the art, such as an ITO conductive glass substrate.
[0085] In this invention, the metal oxide can be a metal oxide conventionally selected in the art for hole transport layers, such as nickel oxide (NiO). x ).
[0086] In this invention, the perovskite active layer is preferably lead-based perovskite, for example, FA. 0.95 Cs 0.05 PbI3.
[0087] In this invention, the electron transport layer can be an electron transport layer conventionally selected in the art, for example, it can be a C 60 (Fullerene).
[0088] In this invention, the electrode is a Cu electrode.
[0089] In this invention, the method for preparing the perovskite solar cell can be a conventional choice in the art, in which the above components are assembled sequentially to obtain the perovskite solar cell.
[0090] In this invention, the method of forming the hole transport layer on the substrate surface can be a conventional choice in the art.
[0091] More preferably, the hole transport layer is formed on the substrate surface by: uniformly spreading NiO on the surface of the ITO substrate. x Thin film, subsequently in NiO x An ethanol solution containing the self-assembled monomolecule material is spread on the surface of the film, spin-coated to form a film, and then annealed at 90-120°C.
[0092] According to the present invention, preferably, the hole transport layer further includes a self-assembled monolayer material containing phosphonic acid groups.
[0093] In this invention, the self-assembled monolayer material can be used alone as one type of self-assembled monolayer in the hole transport layer, or it can be used in combination with self-assembled monolayer materials containing phosphonic acid groups to further reduce the defect density of the perovskite film and improve the photoelectric conversion efficiency, open-circuit voltage (Voc), and fill factor (FF) of the solar cell.
[0094] More preferably, the self-assembled monolayer material containing phosphonic acid groups is selected from at least one of (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid, (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, (2-(9H-carbazole-9-yl)butyl)phosphonic acid, (4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid, 4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl]phosphonic acid, and 4-(9H-9-phenyl-3,3'-dibicarbazole-9-yl)butylphosphonic acid.
[0095] In some specific embodiments of the present invention, the mass ratio of the self-assembled monomolecular material to the self-assembled monolayer material containing phosphonic acid groups is 1:0.8-1.2.
[0096] In this invention, the self-assembled monolayer material and the self-assembled monolayer material containing phosphonic acid groups can be simultaneously molded in the form of a mixture to form a mixed self-assembled monolayer, or they can be molded stepwise to form two separate self-assembled monolayers.
[0097] In some specific embodiments of the present invention, the hole transport layer is formed on the substrate surface by: uniformly spreading NiO on the surface of an ITO substrate. x Thin film, subsequently in NiO x An ethanol solution containing the self-assembled monomolecular material and the self-assembled monolayer material containing phosphonic acid groups is spread on the surface of the film, spin-coated to form a film, and then annealed at 90-120°C.
[0098] In some specific embodiments of the present invention, the hole transport layer is formed on the substrate surface by: uniformly spreading NiO on the surface of an ITO substrate. x Thin film, subsequently in NiO x An ethanol solution containing the self-assembled monolayer material containing phosphonic acid groups is spread on the surface of the film, spin-coated to form a film, and then annealed at 90-120°C; an ethanol solution containing the self-assembled monolayer material is spread, spin-coated to form a film, and then annealed at 90-120°C.
[0099] In this invention, preferably, an ethanol solution containing the self-assembled monolayer material containing phosphonic acid groups and an ethanol solution containing the self-assembled monolayer material are respectively subjected to NiO. x Spin coating of thin films can form a more ordered assembly structure in the hole transport layer, thereby further improving the overall performance of the device.
[0100] The present invention will be described in detail below through examples. All raw materials used in the following examples and comparative examples are commercially available products.
[0101] In the following examples, room temperature refers to 23℃±3℃.
[0102] Me-4PACz refers to (4-(3,6-dimethyl-9H-carbazole-9-yl)butylphosphonic acid).
[0103] Preparation Example 1 A self-assembled monomolecule material A1 was prepared, and its structural formula is as follows: .
[0104] The preparation method is as follows: S1. 0.03 mol of benzo[a]carbazole (compound E1), 0.045 mol of (3-bromopropyl)carbamate tert-butyl ester (compound E2), 0.006 mol of phase transfer catalyst (tetrabutylammonium bromide), and 0.187 mol of KOH were added to a two-necked flask. Under nitrogen protection, 110 mL of acetone and water (acetone to water volume ratio of 10:1) were added to completely dissolve the compounds. The mixture was stirred at 80 °C for 16 h. After the reaction was complete, the mixture was extracted with a mixed solution of dichloromethane and water (dichloromethane to water volume ratio of 1:1). The extracted organic layer was concentrated by rotary evaporation. The crude product was purified by column chromatography to obtain the first intermediate.
[0105]
[0106] S2. Add 1g of the first intermediate to a reaction flask. Under nitrogen protection, add 10 mL of 1,4-dioxane and 0.7 mL of 37wt% HCl. React at 40°C in the dark for 5.5 h. After the reaction is complete, remove the solvent by rotary evaporation, dissolve in ethanol, and then add diethyl ether to precipitate a white solid, giving the second intermediate.
[0107] S3. Dissolve 0.74 g of the second intermediate in 100 mL of ethanol, add 0.002 mol NaOH and react for 1 hour to form a white precipitate of NaCl. After removing NaCl by filtration, add 0.002 mol NaOH to the filtrate under ice bath conditions (0℃±4℃), then add 0.7 g of carbon disulfide, and stir the reaction at room temperature for 24 hours. After the reaction is complete, add HCl to adjust the pH to 5, and then add ethanol and repeatedly evaporate to dryness to obtain the self-assembled monomolecular material A1.
[0108]
[0109] The proton NMR spectrum of the self-assembled single-molecule material A1 is as follows: Figure 1 As shown, by Figure 1 It can be seen that: 1H NMR (400MHz, DMSO) δ 9.06 (d, J=8.5 Hz, 2H), 8.17-8.08 (m, 4H), 8.04-7.89 (m, 4H), 7.74-7.63 (m, 2H), 7.53 (dd, J=13.1, 5.9 Hz, 2H), 4.84 (t, J=7.1 Hz, 2H), 2.88 (dd, J=14.3, 6.1 Hz, 2H), 2.21-2.08 (m, 2H).
[0110] Preparation Example 2 The self-assembled monomolecule material A2 was prepared, and its structural formula is as follows: .
[0111] The preparation method is as follows: S1. 0.03 mol of 3,6-dimethylcarbazole (compound E1), 0.045 mol of (2-bromoethyl)carbamate tert-butyl ester (compound E2), 0.006 mol of phase transfer catalyst (tetrabutylammonium bromide), and 0.187 mol of KOH were added to a two-necked flask. Under nitrogen protection, 110 mL of acetone and water (acetone to water volume ratio of 10:1) were added to completely dissolve the compounds. The mixture was stirred at 55 °C for 12 h. After the reaction was complete, the mixture was extracted with a mixed solution of dichloromethane and water (dichloromethane to water volume ratio of 1:1). The extracted organic layer was concentrated by rotary evaporation. The crude product was purified by column chromatography to obtain the first intermediate.
[0112] S2. Add 1 g of the first intermediate to a reaction flask. Under nitrogen protection, add 10 mL of 1,4-dioxane and 0.7 mL of 37wt% HCl. React at 45°C in the dark for 6 h. After the reaction is complete, remove the solvent by rotary evaporation, dissolve in ethanol, and then add diethyl ether to precipitate the solid, giving the second intermediate.
[0113] S3. Dissolve 0.7 g of the second intermediate in 100 mL of ethanol, add 0.002 mol NaOH and react for 1 hour to form a white precipitate of NaCl. After removing NaCl by filtration, add 0.002 mol NaOH to the filtrate under ice bath conditions (0℃±4℃), followed by 0.7 g of carbon disulfide, and stir at room temperature for 24 hours. After the reaction is complete, add HCl to adjust the pH to 5, then add ethanol and repeatedly evaporate to dryness to obtain the self-assembled monomolecular material A2.
[0114] Preparation Example 3 2 mmol of self-assembled monolayer material A1 was dissolved in 100 mL of ethanol, and an equimolar amount of sodium hydroxide was added. After stirring for 1 hour, the mixture was evaporated to dryness to obtain a yellow solid. After drying, self-assembled monolayer material A3 was obtained, and its structural formula is as follows: .
[0115] Preparation Example 4 The self-assembled monomolecule material A4 was prepared, and its structural formula is as follows:
[0116] S1. In a dried 1L multi-necked round-bottom flask, KOH (6.83 g, 0.122 mol) and 3-bromocarbazole (10.1 g, 0.0406 mol) were added, and the mixture was purged under vacuum / nitrogen three times. 400 mL of acetone, deoxygenated by bubbling under nitrogen, was added with stirring, followed by dropwise addition of bromoethane (8.85 g, 0.0812 mol). The reaction was carried out at 40 °C for 2 hours. After the reaction, the acetone was removed under reduced pressure, the crude product was dissolved in ethyl acetate and washed with 5% HCl, the organic phase was dried, concentrated, and purified by column chromatography to obtain 3-bromo-9-ethyl-9H-carbazole (3BECz) (compound F1). In a Schlenk flask, the above-mentioned 3BECz (7.02 g, 0.0222 mol) and bis(tri-tert-butylphosphine)palladium (0.326 g, 0.640 mmol) were added, and the mixture was evacuated and protected with nitrogen. Anhydrous dioxane solution was added, followed by N-Boc-allylamine (compound F2) (approximately 0.0266 mol) and N-methyldicyclohexylamine (10.8 mL, 0.0666 mol). The reaction was heated at 80 °C for 20 hours. After the reaction, the product containing the double bond was extracted and concentrated. The coupling product was placed in a Schlenk flask, and 10% Pd / C catalyst was added. The double bond was reduced dropwise with triethylsilane in a mixed solvent of dioxane and ethanol under ice bath conditions. The reaction was then carried out at 35 °C for 3 hours. The reaction solution was filtered to remove palladium on carbon, and the product was concentrated and purified to obtain a saturated first intermediate.
[0117] S2. Add the second intermediate to the reaction flask, add 1,4-dioxane and 37wt% HCl under nitrogen protection, and react at 45°C in the dark to remove the Boc protecting group to obtain amine hydrochloride.
[0118] S3. Dissolve the hydrochloride in ethanol, add NaOH to neutralize and react for 1 hour, filter to remove NaCl; add NaOH and carbon disulfide to the filtrate in an ice bath (0℃±4℃), stir and react at room temperature for 24 hours, add HCl to adjust the pH to 5 after the reaction, and evaporate to dryness to obtain the self-assembled monomolecular material A4.
[0119] Example 1 Substrate: Clean the 2 cm × 2 cm ITO conductive glass substrate and perform hydrophilic treatment.
[0120] Hole transport layer: A 20 nm thick NiO layer is uniformly spread on the surface of an ITO substrate. x Thin film, subsequently in NiO xA 50 μL ethanol solution of 0.5 mg / mL Me-4PACz was spread on the film surface, and the film was formed by spin-coating at 3000 rpm for 30 s, followed by annealing at 100 °C for 10 min. On the surface of the Me-4PACz layer, a 50 μL ethanol solution of self-assembled monomolecule material A1 was spin-coated at 3000 rpm for 30 s, followed by annealing at 100 °C for 10 min.
[0121] Subsequently, a perovskite layer (700 nm FA) was deposited. 0.95 Cs 0.05 PbI3), electron transport layer (15 nm C) 60 The perovskite solar cell B1 is assembled with a 5 nm BCP layer and a silver electrode (100 nm).
[0122] Example 2 Substrate: Clean the 2 cm × 2 cm ITO conductive glass substrate and perform hydrophilic treatment.
[0123] Hole transport layer: A 20 nm thick NiO layer is uniformly spread on the surface of an ITO substrate. x Thin film, subsequently in NiO x A 50 μL ethanol solution of 0.5 mg / mL self-assembled monomolecule A1 and 0.5 mg / mL Me-4PACz was spread on the film surface, and the film was formed by spin-coating at 3000 rpm for 30 s and then annealed at 100 °C for 10 min. The mass ratio of self-assembled monomolecule A1 to Me-4PACz was 1:1.
[0124] Subsequently, a perovskite layer (700 nm FA) was deposited. 0.95 Cs 0.05 PbI3), electron transport layer (15 nm C) 60 The perovskite solar cell B2 is assembled with a 5 nm BCP layer and a silver electrode (100 nm).
[0125] Example 3 Substrate: Clean the 2cm×2cm ITO conductive glass substrate and perform hydrophilic treatment.
[0126] Hole transport layer: A 20nm thick NiO layer is uniformly spread on the surface of an ITO substrate. x Thin film, subsequently in NiO x A 50 μL ethanol solution of 0.5 mg / mL self-assembled monomolecule material A1 was spread on the film surface, and the film was formed by spin-coating at 3000 rpm for 30 s and then annealed at 100 °C for 10 min.
[0127] Subsequently, a perovskite layer (700 nm FA) was deposited.0.95 Cs 0.05 PbI3), electron transport layer (15nm C) 60 The perovskite solar cell B3 is assembled with a 5nm BCP layer and a silver electrode (100 nm).
[0128] Example 4 Solar cell B4 was prepared according to the method of Example 1, except that the self-assembled monomolecule material A1 was replaced with A2.
[0129] Example 5 Solar cell B5 was prepared according to the method of Example 1, except that the self-assembled monomolecule material A1 was replaced with A3.
[0130] Example 6 Perovskite solar cell B6 was prepared according to the method of Example 3, except that the self-assembled monomolecule material A1 in the hole transport layer was replaced with the self-assembled monomolecule material A4 obtained in Preparation Example 4.
[0131] Example 7 Perovskite solar cell B7 was prepared according to the method of Example 2, except that during the preparation of the hole transport layer, the spread ethanol solution contained 0.5 mg / mL of self-assembled monomolecule material A1 and 0.25 mg / mL of Me-4PACz, wherein the mass ratio of self-assembled monomolecule material A1 to Me-4PACz was 1:0.5.
[0132] Example 8 Perovskite solar cell B8 was prepared according to the method of Example 2, except that during the preparation of the hole transport layer, the spread ethanol solution contained 0.5 mg / mL of self-assembled monomolecule material A1 and 1.0 mg / mL of Me-4PACz, wherein the mass ratio of self-assembled monomolecule material A1 to Me-4PACz was 1:2.
[0133] Comparative Example 1 Substrate: Clean the 2 cm × 2 cm ITO conductive glass substrate and perform hydrophilic treatment.
[0134] Hole transport layer: A 20 nm thick NiO layer is uniformly spread on the surface of an ITO substrate. x Thin film, subsequently in NiO x A 50 μL ethanol solution of 0.5 mg / mL Me-4PACz was spread on the film surface, and the film was formed by spin-coating at 3000 rpm for 30 seconds and then annealed at 100 °C for 10 min.
[0135] Subsequently, a perovskite layer (700 nm FA) was deposited. 0.95 Cs 0.05PbI3), electron transport layer (15 nm C) 60 The perovskite solar cell DB1 was assembled with a 5 nm BCP layer and a 100 nm silver electrode.
[0136] Comparative Example 2 Substrate: Clean the 2 cm × 2 cm ITO conductive glass substrate and perform hydrophilic treatment.
[0137] Hole transport layer: A 20 nm thick NiO layer is uniformly spread on the surface of an ITO substrate. x Thin film, subsequently in NiO x A 50 μL ethanol solution of the first intermediate of Preparation Example 1 (0.5 mg / mL) was spread on the film surface, and the film was formed by spin-coating at 3000 rpm for 30 s, followed by annealing at 100 °C for 10 min. Substrate: A 2 cm × 2 cm ITO conductive glass substrate was cleaned and hydrophilically treated.
[0138] Subsequently, a perovskite layer (700 nm FA) was deposited. 0.95 Cs 0.05 PbI3), electron transport layer (15 nm C) 60 The perovskite solar cell DB2 was assembled with a 5 nm BCP layer and a 100 nm silver electrode.
[0139] Test Example 1 Under ambient temperature (23±3℃) and AM 1.5 spectral illumination, the current-voltage curves (JV curves) of the perovskite solar cells prepared in the above examples and comparative examples were tested. The open-circuit voltage, short-circuit current, and fill factor were obtained from the JV curves. The results are shown in Table 1.
[0140] Table 1
[0141] Test Example 2 Following the preparation process described in the above embodiments, a 100 nm thick gold electrode was vacuum deposited after depositing a perovskite layer. The IV curve was measured under dark conditions at room temperature, and the defect density N was calculated using the following formula. t The results are shown in Table 2.
[0142] N t =(2εε0V TFL ) / (eL 2 ), Where ε is the relative permittivity of the perovskite material; ε0 is the vacuum permittivity (8.8542 × 10⁻⁶). -14 F / cm); V_TFL is the trap fill limit voltage (unit: V); e is the elementary charge (1.602 × 10⁻⁶).-19 C); L is the thickness of the perovskite active layer (unit: cm).
[0143] Table 2 Defect density of devices fabricated in the test examples
[0144] As can be seen from Tables 1 and 2, introducing the self-assembled monolayer material provided in this application into perovskite solar cells can effectively reduce the defect density on the perovskite surface, thereby improving the open-circuit voltage, short-circuit current, fill factor, and photoelectric conversion efficiency. Combining it with self-assembled monolayer materials containing phosphonic acid groups can further improve the above-mentioned performance.
[0145] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A self-assembled monolayer material, characterized in that, The self-assembled monolayer material has the structure shown in Formula I-1 or Formula I-2; Formula I-1; Formula I-2; Among them, R a1 and R b1 Each is an independently substituted or unsubstituted carbazole group; R a2 and R b2 Each is independently a C1-C8 alkylene group or a C6-C12 arylene group; M + It is a monovalent cation.
2. The self-assembled monolayer material according to claim 1, wherein, R a1 and R b1 Each is an independent group represented by Formula II; Formula II; Among them, R 1-1 and R 1-2 Each can be independently H, phenyl, methyl, or methoxy; And / or, R a2 and R b2 Each is independently a C2-C4 alkylene or phenylene; And / or, M + For Li + Na + K + 、Rb + Cs + NH4 + R3NH3 + Or (R4)4N + In this context, R3 and R4 are each independently a C1-C3 alkyl group.
3. The self-assembled monolayer material according to claim 1 or 2, wherein, The self-assembled monolayer material has the structure shown in Formula III-1, Formula III-2 or Formula III-3; Formula III-1; Formula III-2; Formula III-3; Formula III-4.
4. A method for preparing a self-assembled monolayer material, characterized in that, The preparation method includes: S1-1, In the presence of a first inorganic base and a phase transfer catalyst, compound E1 and compound E2 are contacted in a first solvent to carry out a first reaction, yielding a first intermediate; S1-2. In the presence of a palladium catalyst, compound F1 and compound F2 are brought into contact for a cross-coupling reaction, followed by a reduction reaction in the presence of a reducing agent and a reduction catalyst to obtain the first intermediate. S2. In the second solvent, the first intermediate obtained in step S1-1 or step S1-2 is contacted with an acid to carry out a second reaction to obtain the second intermediate. S3. In the third solvent, the second intermediate is contacted with the second inorganic base to carry out the third reaction. The liquid after the reaction is reacted with carbon disulfide in the presence of the third inorganic base to carry out the fourth reaction. After the reaction, the pH of the system is adjusted to acidic. After solid-liquid separation, the self-assembled monolayer material 1 is obtained. S4. Optionally, the above self-assembled monolayer 1 is contacted with an alkaline compound in a fourth solvent to carry out a fifth reaction, and after solid-liquid separation, the self-assembled monolayer material 2 is obtained. Among them, compound E1 has the structure shown in formula (1); Equation (1); Compound E2 has the structure shown in formula (2); Equation (2); Compound F1 has the structure shown in formula (3); Equation (3); Compound F2 has the structure shown in formula (4); Equation (4); Where X is a halogen; R2' is a C1-C8 alkylene group or a C6-C12 arylene group; R is a C2-C18 alkyl group; R' 1-1 、R' 1-2 、R'' 1-1 、R'' 1-2 Each can be independently H, phenyl, methyl, or methoxy; R1 is a C1-C8 alkyl group; R3 is a C1-C8 alkyl group, and p is an integer from 1 to 10.
5. The preparation method according to claim 4, wherein, In step S1-1, the molar ratio of compound E1 to compound E2 is 1:1-2; And / or, in step S1-1, the phase transfer catalyst is selected from at least one of tetrabutylammonium bromide, tetrabutylammonium chloride, and benzyltriethylammonium chloride. And / or, in step S1-1, the molar ratio of the phase transfer catalyst to compound E1 is 0.1-0.2:1; And / or, in steps S1-2, the molar ratio of compound F1 to compound F2 is 1:1-1.5; And / or, in steps S1-2, the molar ratio of the palladium catalyst to the compound F1 is 0.01-0.05:1; And / or, the molar ratio of the acid to compound E1 is 3-4:1; And / or, the molar ratio of carbon disulfide to compound E1 is 1-1.2:1; And / or, the first inorganic base, the second inorganic base, and the third inorganic base are each independently KOH and / or NaOH; And / or, the acid is selected from at least one of hydrochloric acid, sulfuric acid, and phosphoric acid.
6. The preparation method according to claim 4 or 5, wherein, In step S1-1, the conditions for the first reaction include: being carried out under a protective atmosphere, at a temperature of 50-80°C, and for a time of 8-16 hours; And / or, in steps S1-2, the conditions for the cross-coupling reaction include: being carried out under a protective atmosphere, at a temperature of 75-85℃, for a time of 16-24h; And / or, in steps S1-2, the conditions for the reduction reaction include: a temperature of 30-40℃ and a time of 2-4h; And / or, the conditions for the second reaction include: being carried out in the dark and under a protective atmosphere, at a temperature of 40-50°C, for a time of 5-6 h; And / or, the duration of the third reaction is 1-2 h; And / or, the fourth reaction takes 1-2 hours.
7. A self-assembled monolayer material prepared by the preparation method according to any one of claims 4-6.
8. The application of the self-assembled monolayer material according to any one of claims 1-3 and 7 in perovskite solar cells.
9. A perovskite solar cell, characterized in that, The perovskite solar cell includes: a substrate, a hole transport layer, a perovskite active layer, an electron transport layer, and electrodes; The hole transport layer comprises a metal oxide and a self-assembled monolayer material as described in any one of claims 1-3 and 7.
10. The perovskite solar cell according to claim 9, wherein, The hole transport layer further includes: a self-assembled monolayer material containing phosphonic acid groups; Preferably, the self-assembled monolayer material containing phosphonic acid groups is selected from at least one of (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid, (2-(9H-carbazole-9-yl)ethyl)phosphonic acid, (2-(9H-carbazole-9-yl)butyl)phosphonic acid, (4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)ethyl)phosphonic acid, (4-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl)phosphonic acid, 4-(2,7-dibromo-9,9-dimethylacridin-10(9H)-yl)butyl]phosphonic acid, and 4-(9H-9-phenyl-3,3'-dibicarbazole-9-yl)butylphosphonic acid; Preferably, the mass ratio of the self-assembled monomolecular material to the self-assembled monolayer material containing phosphonic acid groups is 1:0.8-1.2.